Automatic Continuity Test Machine (CT) Using Proximity Sensors, Photoelectric Sensors and Programmable Logic Controllers (PLC) Systems: The case at PT. “V” Batam Indonesia - Jhon Hericson Purba; Irwanto Zarman Putra; Ridwan Ridwan; Hari Salam (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
Continuity test Machine (CT) is a tool for detecting damage to the current connection on the AC plug cable. The problem with PT “V” is that it still uses a manual system. So that it is updated to an automatic continuity test machine by manual measurement using a